Long-Term outcomes of uncut roux-en-Y anastomosis in laparoscopic distal gastrectomy: A retrospective analysis - Zhu, Guangxu; Zhou, Shengjie; Shen, Xiaoru; Qu, Jianjun (Frontiers in Surgery, 2023)
Background: Uncut Roux-en-Y (U-RY) has been increasingly used in radical gastric cancer surgery, but it is still in the exploratory stage. There is insufficient evidence for its long-term efficacy. Methods: From January 2012 to October 2017, a total of 280 patients diagnosed with gastric cancer were eventually included in this study. Patients undergoing U-RY were assigned to the U-RY group, while patients undergoing BillrothII with Braun (B II+Braun) were assigned to the B II+Braun group. Results: There were no significant differences between the two groups in operative time, intraoperative blood loss, postoperative complications, first exhaust time, time to liquid diet, and length of postoperative hospital stay (all P>0.05). Endoscopic evaluation was performed 1 year after surgery. Compared to B II+Braun group, the uncut Roux-en-Y group had significantly lower incidences of gastric stasis [16.3% (15/92) vs. 28.2% (42/149), χ2=4.448, P=0.035], gastritis [13.0% (12/92) vs. 24.8% (37/149), χ2=4.880, P=0.027] and bile reflux [2.2% (2/92) vs. 20.8% (11/149), χ2=16.707, P<0.001], and the differences were statistically significant. The questionnaire was completed 1 year after surgery,the QLQ-STO22 scores showed that, the uncut Roux-en-Y group had a lower pain score(8.5±11.1 vs 11.9±9.7, P=0.009) and reflux score(7.9±8.5 vs 11.0±11.5, P=0.012), and the differences were statistically significant (P<0.05). However, there was no significant difference in overall survival (P=0.688) and disease-free survival (P=0.505) between the two groups. Conclusion: Uncut Roux-en-Y has the advantages of better safety, better quality of life and fewer complications, and is expected to be one of the best methods for digestive tract reconstruction.